Efektivitas Scapular Stabilization Exercise pada Forward Head Posture : Literature Review - Karang, Ni Nyoman Melani; Adyasputri, A A I Ayesa Febrinia; Antyesti, Aryaning Dwi; Diahputri, Ni Made Nuari (LPPM Universitas Dhyana Pura, 2025)
Background: Musculoskeletal disorders are among the health problems increasingly observed across various age groups. One of the commonly encountered conditions is forward head posture (FHP). This condition has the potential to cause postural deviations, functional limitations, and musculoskeletal pain. Exercise therapy is a widely used approach to address FHP. Specifically, Scapular Stabilization Exercise (SSE) is a training method that can improve postural alignment and reduce associated symptoms. This literature review aims to analyze the effects of SSE on individuals with FHP based on findings from relevant research studies. Methods: This article was developed using a literature review methodology, which involved searching and examining various sources related to the topic obtained through databases such as Google Scholar, PEDro, and PubMed. A total of five articles were reviewed for this study. Results: Based on previous research, SSE can be an effective exercise therapy option for individuals with FHP. Conclusion: Scapular Stabilization Exercise (SSE) has proven effective as an exercise therapy approach for FHP. This intervention is known to increase Cervical Vertebral Angle (CVA), and reduce pain and disability in the short term.